Orthotic Design through 3D Reconstruction: A Passive-Assistance Ankle–Foot Orthotic - A. L. Darling; W. Sun (Applied Bionics and Biomechanics)
Current methods of designing and manufacturing custom orthotics include manual techniques such as casting a limb in plaster, making a plaster duplicate of the limb to be treated and forming a polymer orthotic directly onto the plaster model. Such techniques are usually accompanied with numerous postmanufacture alterations to adapt the orthotic for patient comfort. External modeling techniques rely heavily on the skill of the clinician, as the axes of rotation of any joint are partially specified by the skeletal structure and are not completely inferable from the skin, especially in cases where edema is present. Clinicians could benefit from a simultaneous view of external and skeletal patient-specific geometry. In addition to providing more information to clinicians, quantification of patient-specific data would allow rapid production of advanced orthotics, requiring machining rather than casting. This paper presents a supplemental method of orthotic design and fitting, through 3D reconstruction of medical imaging data to parameterise an orthotic design based on a major axis of rotation, shape of rigid components and placement of skin contact surfaces. An example of this design approach is shown in the design of an ankle–foot orthotic designed around the computed tomography data from the Visible Human Project.